Pre-outbreak forest conditions mediate the effects of spruce beetle outbreaks on fuels in subalpine forests of Colorado - Mietkiewicz, Nathan; Kulakowski, Dominik; Veblen, Thomas T. (Ecological applications, 2018)
Over the past 30 years, forest disturbances have increased in size, intensity, and frequency globally, an d are predicted to continue increasing due to climate change, potentially relaxing the constraints of vegetation properties on disturbance regimes. However, the consequences of the potentially declining importance of vegetation in determining future disturbance regimes are not well understood. Historically, bark beetles preferentially attack older trees and stands in later stages of development. However, as climate warming intensifies outbreaks by promoting growth of beetle populations and compromising tree defenses, smaller diameter trees and stands in early stages of development now are being affected by outbreaks. To date, no study has considered how stand age and other pre-outbreak forest conditions mediate the effects of outbreaks on surface and aerial fuel arrangements. We collected fuels data across a chronosequence of post-outbreak sites affected by spruce beetle (SB) between the 1940s and the 2010s, stratified by young (<130 yr) and old (>130 yr) post-fire stands. Canopy and surface fuel loads were calculated for each tree and stand, and available crown fuel load, crown bulk density, and canopy bulk densities were estimated. Canopy bulk density and density of live canopy individuals were reduced in all stands affected by SB, though foliage loss was proportionally greater in old stands as compared to young stands. Fine surface fuel loads in young stands were three times greater shortly (<30 yr) following outbreak as compared to young stands not affected by outbreak, after which the abundance of fine surface fuels decreased to below endemic (i.e., non-outbreak) levels. In both young and old stands, the net effect of SB outbreaks during the 20th and 21st centuries reduced total canopy fuels and increased stand-scale spatial heterogeneity of canopy fuels following outbreak. Importantly, the decrease in canopy fuels following outbreaks was greater in young post-fire stands than in older stands, suggesting that SB outbreaks may more substantially reduce risk of active crown fire when they affect stands in earlier stages of development. The current study shows that the effects of SB outbreaks on forest structure and on fuel profiles are strongly contingent on pre-outbreak conditions as determined by pre-outbreak disturbance history.